Positive Deviance Approach and Supplementary Nutrition Under ICDS Scheme on Improvement of Nutritional Status Of 2–6 Year Children in Rural Bangalore - Imran, Mohammed; Subramanian, Mangala; Subrahmanyam G; Seeri, Jayashree; Pradeep C; Jayan, Mini (National Journal of Community Medicine, 2014)
Introduction: Childhood malnutrition is a significant health problem in India and important cause for childhood morbidity and mortality. Lack of knowledge about child feeding contributes significantly to poor nutritional status among children. A system to deliver nutrition education effectively would be of value in India. Hence, the present study was designed to assess nutritional status of 2 to 6 year Anganwadi children and to evaluate effect of nutrition education and supplementary nutrition on nutritional status of malnourished Anganwadi children Methods: An Interventional study was carried out in rural anganwadi centres selected by cluster sampling technique. Intervention was done in the form of Nutrition education based on positive deviance approach, supplementary nutrition and supervision. Weight for age of study participants was measured every quarter for a period of one year. Results: The prevalence of underweight initially was 47.3%. After intervention prevalence reduced to 43%, 40%, 32% and 30 % during first, second, third and fourth quarter assessment. The improvement was significant between baseline and first quarter assessment (P<0.01), between second and third quarter assessment (P<0.001) and between third and fourth quarter assessment (P = 0.03) though not significant between first and second quarter assessment. Conclusion: Nutrition education based on positive deviance approach and supplementary nutrition helps to improve the nutritional status of the anganwadi children.